-3(5s-6)-18=-3(7s+2)-3

Simple and best practice solution for -3(5s-6)-18=-3(7s+2)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(5s-6)-18=-3(7s+2)-3 equation:


Simplifying
-3(5s + -6) + -18 = -3(7s + 2) + -3

Reorder the terms:
-3(-6 + 5s) + -18 = -3(7s + 2) + -3
(-6 * -3 + 5s * -3) + -18 = -3(7s + 2) + -3
(18 + -15s) + -18 = -3(7s + 2) + -3

Reorder the terms:
18 + -18 + -15s = -3(7s + 2) + -3

Combine like terms: 18 + -18 = 0
0 + -15s = -3(7s + 2) + -3
-15s = -3(7s + 2) + -3

Reorder the terms:
-15s = -3(2 + 7s) + -3
-15s = (2 * -3 + 7s * -3) + -3
-15s = (-6 + -21s) + -3

Reorder the terms:
-15s = -6 + -3 + -21s

Combine like terms: -6 + -3 = -9
-15s = -9 + -21s

Solving
-15s = -9 + -21s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '21s' to each side of the equation.
-15s + 21s = -9 + -21s + 21s

Combine like terms: -15s + 21s = 6s
6s = -9 + -21s + 21s

Combine like terms: -21s + 21s = 0
6s = -9 + 0
6s = -9

Divide each side by '6'.
s = -1.5

Simplifying
s = -1.5

See similar equations:

| 3/4x2=21 | | 5X/6-3/8=7X/4 | | 16x-1024/x2 | | 4(n-25)=9n | | 18000+36000r+18000r^2=0 | | 100-207/8 | | 24.6176=3.14r^2 | | 4x-12=7+7x-4 | | 0.8=5.8/x | | 1.2x+5=3.4 | | 2x^3+3x^2-29x-60=0 | | (2/3)/(3/11) | | 18000+36000r+18000r^2=0 | | 4x=10x-36 | | 6(w-2)-4=-2(-8w+9)-2w | | x=15-4(3+32) | | -14x-67=-11 | | p(-3)=3x^2-5x+7 | | P=4n+32 | | 5(x+1)+4(x+4)=75 | | -7+5=48 | | 4x+15+43=90 | | -0.5-2.7=-1.7 | | 6u+6-2(-4u-1)=2(u-3) | | -12x-10=-11x+16 | | Sin^4(3x/2) | | 6x^2y+8xy+2=0 | | 7(2b+1)-3b=29 | | 4a(a^4)7a=a(4a^3)+20 | | 6x^2y+8xy+2= | | 4x/4=29/8 | | 20/10=N/2 |

Equations solver categories